Dendrodoristerol, a cytotoxic C20 steroid from the Vietnamese nudibranch mollusk Dendrodoris fumata. Issue 2 (1st February 2020) - Huong, Pham Thi Mai; Phong, Nguyen Viet; Thao, Nguyen Phuong; Binh, Pham Thanh; Thao, Do Thi; Thanh, Nguyen Van; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Thung, Do Cong; Minh, Chau Van
Abstract: Using various chromatographic separations, four steroids including one new C20 steroid namely dendrodoristerol (1 ), were isolated from the Vietnamese nudibranch mollusk Dendrodoris fumata . The structure elucidation was confirmed by combination of spectroscopic experiments including 1D and 2D NMR, HR QTOF MS, and CD. Compound 1 was found to exhibit significant in vitro cytotoxic activity against six human cancer cell lines as HL-60, KB, LU-1, MCF-7, LNCaP, and HepG2. In addition, 1 induced HL-60 cancer cell death by apoptosis and necrosis. Graphical Abstract: